Financial market frictions in the 21st century : how mandatory pension contributions impact investment decisions and cost of capital - Mendes, Maria Maia (2024)
This dissertation investigates the influence of mandatory pension contributions on U.S. companies' Weighted Average Cost of Capital (WACC) and Capital Expenditures (CapEx). Motivated by demographic shifts, a pivotal regulatory change in 2006, known as the “Pension Protection Act 2006” (PPA 2006), aimed to address the aging U.S. population, requiring companies with pension plans to enhance their funding status. The research hypotheses expected mandatory pension contributions to positively impact WACC and negatively impact CapEx. Utilizing a sample of S&P 500-listed companies reporting pension funds, spanning 1991 to 2022, the study navigates four major economic crises – the 2008/2009 financial crisis followed by the European debt crisis, the COVID-19 crisis and the current crisis arising from the conflict between Russia and Ukraine. This temporal breadth provides a robust foundation for understanding how mandatory pension contributions impact financial decisions across diverse economic landscapes. Main findings support the expectation that mandatory pension contributions negatively impact CapEx. This effect was reinforced after the regulatory change in 2006, indicating a heightened sensitivity of companies to investment decisions post-legislation. However, when examining the influence of mandatory pension contributions on WACC, the results reveal a counterintuitive negative coefficient, suggesting a complex interplay influenced by the regulatory changes of 2006. To validate these findings, several robustness checks were conducted.